(4/6)x=(5/6)y

Simple and best practice solution for (4/6)x=(5/6)y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4/6)x=(5/6)y equation:


x in (-oo:+oo)

(4/6)*x = (5/6)*y // - (5/6)*y

(4/6)*x-((5/6)*y) = 0

(4/6)*x+(-5/6)*y = 0

2/3*x-5/6*y = 0 // + -5/6*y

2/3*x = -(-5/6*y) // : 2/3

x = (-(-5/6*y))/2/3

x = 5/4*y

x = 5/4*y

See similar equations:

| (4/6)x(5/6)y | | (X-3)(2x+9)=9(3x+2) | | y-10=9y-6 | | ml=7.3l | | 9w=2*9w | | 4cosx-2=cosx | | 2^-1=1/64 | | 9x^2-9x-15=0 | | 6+2x+3y=48 | | 7b+2a-(3a+2b)= | | 4x-6=2(x+1) | | (X-786)(x+4)=0 | | (X-393)(x+4)=0 | | 2x+5(2.5)=20 | | 27=(27-15x)*2 | | 5779/19= | | -100=0.1x(30+-1x) | | -100=0.1(30-x) | | arccos(3/5) | | 4--7= | | 65+70=78 | | 12/x=6/11 | | x/2=3/10 | | 12/x=6/9 | | -55+b+39.68=-71.03 | | -55+b+39.68=71.03 | | 10z+1=3z+6 | | 5x-80x^2=0 | | 3x^3-9=0 | | 1=8tan(2x+1)-3 | | 4/25-x^2/81 | | 4(m+1)= |

Equations solver categories